Answer: C. and
Step-by-step explanation: if a function f(x) has g(x) as its inverse then it satisfies fog(x)=x and gof(x)=x
C. f(x)= and g(x)=
fog(x)=f()
=
=x
gof(x)=g()
=
=x
hence C. is the pair of inverse functions
Answer:
coordinates of its image
A' = ( -4, -1)
B' =( -3, -3)
C' = ( 0, 2)
Step-by-step explanation:
Reflect in y-axis means mirror it's points in the y -axis.
This means that the x coordinate of each point, changes only. Any mirrored point in the y-axis, will change only, by multiplying the x-coordinate by -1.
(Remember, zero multiplied by -1 remains 0).
Given are these points A, B, and C.
A = (4, -1)
B = (3,-3)
C = (0, 2)
After mirroring in the y- axis you get:
A' = ( -4, -1)
B' =( -3, -3)
C' = ( 0, 2)
Step-by-step explanation:
slope= -1/2
y intercept= 2
y=mx+b
m is the slope and b is the y intercept.
Integrating gives
To compute the integral, substitute , so that . Then
Since for all , we can drop the absolute value, so we end up with
Given that , we have
so that